2019
DOI: 10.1158/1078-0432.ccr-18-3160
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Randomized Study of Neoadjuvant Letrozole Plus Alpelisib for Hormone Receptor-Positive, Human Epidermal Growth Factor Receptor 2-Negative Breast Cancer (NEO-ORB)

Abstract: Purpose: Addition of alpelisib to fulvestrant significantly extended progression-free survival in PIK3CA-mutant, hormone receptor-positive (HR+) advanced/metastatic breast cancer in the phase III SOLAR-1 study. The combination of alpelisib and letrozole also had promising activity in phase I studies of HR+ advanced/metastatic breast cancer. NEO-ORB aimed to determine if addition of alpelisib to letrozole could increase response rates in the neoadjuvant setting. Experimental Design: Postmenopausal women with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 58 publications
0
69
0
4
Order By: Relevance
“…neoadjuvant setting, a PIK3CA-mut has no predictive value for treatment with the pan-PI3Ki pictilisib (OPPORTUNE trial) or the a-selective PI3Ki alpelisib (NEO-ORB trial), but seems to predict benefit from the b-sparing PI3Ki taselisib (LORELEI trial) [5,6,12,18].…”
Section: Potential Biomarkers To Predict the Benefit From Pi3kimentioning
confidence: 99%
See 2 more Smart Citations
“…neoadjuvant setting, a PIK3CA-mut has no predictive value for treatment with the pan-PI3Ki pictilisib (OPPORTUNE trial) or the a-selective PI3Ki alpelisib (NEO-ORB trial), but seems to predict benefit from the b-sparing PI3Ki taselisib (LORELEI trial) [5,6,12,18].…”
Section: Potential Biomarkers To Predict the Benefit From Pi3kimentioning
confidence: 99%
“…The OPPORTUNE trial suggested that patients with progesterone receptor-negative or luminal B tumours may benefit more from pictilisib due to the drug's antiproliferative effect [5,6], but this was not demonstrated in the NEO-ORB trial [18].…”
Section: Other Potential Biomarkers Of Responsementioning
confidence: 99%
See 1 more Smart Citation
“…The use of endocrine-based therapy in the neoadjuvant situation represents an alternative to chemotherapy for a certain patient population and is currently being investigated intensively in studies 51 , 52 , 53 . In particular, a neoadjuvant study can investigate how certain resistance mechanisms are overcome by CDK4/6 inhibitors.…”
Section: Neoadjuvant Therapymentioning
confidence: 99%
“…Der Einsatz endokrin basierter Therapie in der neoadjuvanten Situation stellt für eine gewisse Patientinnenpopulation eine Alternative zur Chemotherapie dar und wird derzeit in Studien intensiv untersucht 51 , 52 , 53 . Insbesondere kann in einer neoadjuvanten Studie untersucht werden, wie durch CDK4/6-Inhibitoren gewisse Resistenzmechanismen überwunden werden.…”
Section: Neoadjuvante Cdk4/6-inhibitortherapieunclassified